Factors on curving unripe fresh fruit bunch of oil palm towards oil extraction rate at mill / Muhammad Hazim Ramli - Ramli, Muhammad Hazim (Faculty of Plantation and Agrotechnology, 2015)
Decreasing percentage of oil extraction rate of company has caused many problems especially towards the company that the decreasing of profit . The decreasing of oil extraction rate are due to increase in the number of unripe fresh fruit bunch that are sent to the mill from the estate . Increasing number of unripe fresh fruit bunch that can be recognized by its color which is blackish reddish in color has to do with the management of the company. In order to curve the unripe fruit being sent to the mill , management are responsible to manage it .Under the management, several reasons or variable are used in order to measure which on mostly influence the factors on management to curve of unripe fruit of the organization .Fresh fruit bunch standard operating procedures of the company are one of the variable also skills of the worker and also knowledge of the worker are measured on what are the reason to the increase of unripe fruit being harvested and also to measure which of the variables most influence towards curving unripe fruit being sent to the mill . Method of questionnaire and interview with the respondent are used in order to obtain the data as well as fulfilling the needs for each variable . A number of 134 respondent was interviewed from the companies such as FELDA , 101 and RISDA Plantation all in the area of Me1aka .Severa1 analysis are used to measure up the reliability of the questionnaire and also normality analysis are used to measure up the normal distribution of each data .Corre1ation analysis are also used to measure up the strength of independent variable and the dependent variable of the study. The independent variable includes the fresh fruit bunch standard operating procedure , skills of worker and knowledge of worker . The dependent variable is the factor of curving unripe fresh fruit bunch to the mill . Regression analysis are also used to measure up in which of the independent variable mostly influence the dependent variable. Another analysis used are ANOYA analysis that is to check whether there are any significant difference of different management towards the improvement of factors on curving unripe fruit sent to the mill .The results and finding of the study can help improve the management of companies to reduce the number of unripe fresh fruit bunch from being sent to the mill as will the increase the percentage of oil extraction rate and will then increase the profitability of the company . The study can point out on which factor mostly influence the factors on to curve unripe fresh fruit bunch. Limitation of the study was also stated to know what limits the progress of the study as well as future improvement of the study to be conducted in the future.